2015
DOI: 10.1111/bdi.12340
|View full text |Cite
|
Sign up to set email alerts
|

Test–retest reliability of schizoaffective disorder compared with schizophrenia, bipolar disorder, and unipolar depression—a systematic review and meta‐analysis

Abstract: In clinical practice and research, schizoaffective disorder's comparatively low diagnostic reliability should lead to increased efforts to correctly diagnose the disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
11

Year Published

2016
2016
2025
2025

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 89 publications
(94 reference statements)
1
27
0
11
Order By: Relevance
“…In one out of three patients with SAD at first assessment, the diagnoses will change over time. This finding is in line with a systematic literature review and meta‐analysis in which we found a Cohen's kappa reliability of 0.5 for SAD, compared to about 0.7 for its three main differential diagnoses (schizophrenia, bipolar disorder, and unipolar depression) . Clinically, this finding is important because treatment needs to be adjusted according to diagnostic change.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In one out of three patients with SAD at first assessment, the diagnoses will change over time. This finding is in line with a systematic literature review and meta‐analysis in which we found a Cohen's kappa reliability of 0.5 for SAD, compared to about 0.7 for its three main differential diagnoses (schizophrenia, bipolar disorder, and unipolar depression) . Clinically, this finding is important because treatment needs to be adjusted according to diagnostic change.…”
Section: Discussionsupporting
confidence: 90%
“…The search algorithm has been described elsewhere in depth . In short, we searched Medline (via PubMed), Embase (via Ovid), and PsycINFO (via Ebsco host) databases from their inception until 28 May 2014, for rediagnosis studies of patients with SAD.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of classifier accuracy for SZA is important, since the diagnosis of SZA as a distinct entity remains a contentious issue in psychiatry (Heckers, 2009;Santelmann et al, 2015). Indeed, it has been argued that rather than being a separate disorder, SZA reflects either a) a comorbid syndrome stemming from within SZ or BD themselves, or b) the intersection of a psychiatric continuum representing the milder end of the former disorder and the more extreme end of the latter (Malhi et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…However, there is evidence of reasonable test-retest of MDD symptoms and diagnosis across instruments, or between clinician [600][601][602][603]. Reliability of diagnosis is even higher for schizophrenia [604], while ICV putamen and hippocampus volume show very good test-retest [332] and agreement between processing software [76]. Consequently, differences in measurement error are unlikely to completely cause the differences observed in Figure 43 [592].…”
Section: Resultsmentioning
confidence: 99%